INSIGHTS INTO THE MOLECULAR DOCKING STUDY OF WEDELOLACTONE TO IMPROVE THE PERFORMANCE OF COMPUTER-AIDED DRUG DESIGN - RICHA ANAND; RICHA RAGHUWANSHI (International Journal of Pharma and Bio Sciences, 2016)
The structure based docking of a ligand molecule to a biological receptor urge for an efficient sampling of possible docked poses in the binding vicinity of the target molecule to assure the optimal binding. A computational molecular docking is commonly used to study the molecular interactions in drug design. Most of the docking algorithms use receptor as rigid and ligand as flexible molecule which may lead to decrease in an accuracy of predicted docked poses. The MD simulation gives an insight into the dynamics of biological macromolecules. Therefore prior to molecular docking dynamics study of the receptor molecule may result in more accurate docking results. The contribution of MD (Molecular Dynamic) simulation along with docking in a study on human 5-LOX (lipoxygenase), the key player in the inflammatory cascade, was evaluated. Using MD simulation and web based automated molecular docking procedure, it was found that short MD simulations prior to molecular docking significantly improved the docking results. Extensive analysis of the results has revealed that MD simulation generated snapshots have shown the better binding affinity towards wedelolactone in contrast to its crystal structure selected from PDB.